The method of problematization in the teacher-learning process applied to distance learning technology: A brazilian experience - Alves de Vilar, Rosana Lucia (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2017)
This paper analyzes use of the problematization method in a distance learning experiment carried out with health professionals in Brazil through the use of integrated media. This method is aimed at the acquisition of knowledge linked to social context, enabling a confrontation between experienced practices and proposed content. The results obtained confirmed the functionality of this method as a teaching option using media that connects the virtual learning environment, the printed book and tutor guidance. On completion of the course, the elaborated intervention projects were successful indicating meaningful learning, with the possibility of making changes to the practices.